2018
DOI: 10.1186/s12936-018-2589-6
|View full text |Cite
|
Sign up to set email alerts
|

Outreach training and supportive supervision for malaria case management in Zambia: the effects of focused capacity building on indicators of diagnostic and clinical performance

Abstract: BackgroundAccurate diagnosis of malaria and reduced reliance on presumptive treatment are crucial components of quality case management. From 2008 to 2012, the Improving Malaria Diagnostics project, in collaboration with the Zambia National Malaria Control Centre, implemented an external quality assurance scheme partially comprised of outreach training and supportive supervision (OTSS) in an effort to improve malaria case management across a spectrum of health facilities performing laboratory-based malaria dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…Additionally, the study findings lend credence to the importance of availing all health care workers with guidelines relevant to malaria case management promoting adherence to guidelines. Effective supervision systems for HCW at both public and private facilities should be emphasized as these realign practice to standards [ 53 ]. For the private sector, challenges are unique, driven by lack of knowledge, the desire to profit, and lack of incentive to adhere to guidelines calling for regulation and innovative and sustainable strategies that promote adherence to guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the study findings lend credence to the importance of availing all health care workers with guidelines relevant to malaria case management promoting adherence to guidelines. Effective supervision systems for HCW at both public and private facilities should be emphasized as these realign practice to standards [ 53 ]. For the private sector, challenges are unique, driven by lack of knowledge, the desire to profit, and lack of incentive to adhere to guidelines calling for regulation and innovative and sustainable strategies that promote adherence to guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…More efforts are required to strengthen the capacity of health workers in both public and private sectors. Studies have shown that this can be achieved through on job training programs, supportive supervision, and reliable supplies of quality reagents, electricity and establishment of an external quality assurance scheme [4, 9, 13, 1517, 36, 38].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report 30–96% of parasite negative patients being treated for malaria [1012]. Therefore, there is a need for training of microscopists and supportive supervision to improve malaria microscopy competencies in health facilities [4, 1417].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a holistic conception requires viewing supervision not just as a dyadic relationship between a supervisee and their immediate line supervisor,10–14 but rather as a system operating at several levels with a range of functions involving different actors and relationships and forms of interaction, for example, one-on-one, group and peer supervision, and so on, simultaneously 7 9. In this sense, supervision can be thought of as a set of relationships embedded in the wider context of social and professional relationships and hierarchies within the health system.…”
Section: Introductionmentioning
confidence: 99%